Information Metasurface Technology-enabled Integrated Passive Wireless Communication System Based on Synthetic Aperture Radar - Hua LI; Kaiyu LIU; Yunkai DENG; Zhenning LI; Chao LUO; Jichen LI; Taoyu REN; Yao CHEN; Kaijiang XU (Leida xuebao)
The integration technology of satellite communications and spaceborne Synthetic Aperture Radar (SAR) remote sensing aims to combine communication and remote sensing functionalities, enabling simultaneous data transmission and remote sensing imaging to meet the demands of efficient, covert, and secure information transfer, enhancing system multifunctionality. However, due to significant differences between the waveform characteristics, transceiver design, and signal processing algorithms of the technologies, integrating communication and remote sensing in spaceborne systems presents numerous challenges. This study proposes a passive wireless communication system based on information metasurface technology, combined with SAR echo modulation methods, to innovatively achieve the deep integration of ground-to-space communication and spaceborne SAR remote sensing. The system precisely modulates the scattering parameters of SAR echoes to enable passive wireless communication without affecting the quality of SAR imaging. Additionally, by leveraging electromagnetic backscatter properties instead of active transmission mechanisms, the system effectively ensures the electromagnetic concealment and information security of the communication link. A series of scene simulation experiments and spaceborne SAR data experiments were performed, which validated the system’s feasibility and effectiveness. Results indicate that while maintaining compatibility with traditional SAR waveform structures, the proposed system successfully achieved the synchronous operation of ground-to-space data transmission and spaceborne SAR imaging. The core objective of this research was to promote the deep integration of spaceborne SAR remote sensing systems and wireless communication technologies, aiming for the efficient utilization of spectrum resources and exploring the application of information metasurface technology in integration of communication and remote sensing systems, providing new research perspectives and technological potential in this field.